Cell : A molecular approach - Cooper, Geoffrey M; Hausman, Robert E (Sunderland : Sinauer Associates, 2013)
The Cell presents current comprehensive science in a readable and cohesive text that students can master in the course of one semester. The Sixth Edition retains the overall organization, themes, and special features of the previous edition, including Key Experiment and Molecular Medicine essays, chapter sidebars that highlight areas of interest and clinical applications, and end-of-chapter questions with answers at the back of the book. Yet, the Sixth Edition has been updated throughout to reflect major advances since publication of the previous edition in 2009. In addition, many of the figures have been revised to achieve a contemporary graphic look. The book is supported by a Companion Website (http://sites.sinauer.com/cooper6e/) which offers a wealth of study and review material as well as rich multimedia resources, including: quizzes, animations of key concepts and processes, chapter summaries, interactive micrographs and a collection of video microscopy showing biological processes in action.
References 757-760p.; Glossary 773-796p.; Illustration credits 797-798p.; Index 799-832p.-
Keywords: Plasma membrane; RNA Synthesis; Cencer